2016
DOI: 10.1016/j.susc.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silica films on Ru(0001): A LEEM/PEEM study

Abstract: We use an aberration corrected spectro-microscope, the low energy electron microscope/photoelectron emission microscope (LEEM/PEEM) SMART, to follow the preparation and structure of a bilayer silica film on Ru(0001) as a function of temperature and oxidation conditions. This allows us to analyze the growth process at different length scales in order to judge on the overall quality and the morphology of the film. It is found that the film growth occurs in a crystalline and a vitreous phase as previously discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 40 publications
(34 reference statements)
3
38
0
Order By: Relevance
“…Both the intensity and the full width at the half maximum (FWHM) of the O 1 s and Si 2p remain unchanged, indicating that the chemical composition and bonding configuration of the silica film stay intact. The increase in binding energies can be attributed to changes of the chemical states on the Ru substrate [13,37,38]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Both the intensity and the full width at the half maximum (FWHM) of the O 1 s and Si 2p remain unchanged, indicating that the chemical composition and bonding configuration of the silica film stay intact. The increase in binding energies can be attributed to changes of the chemical states on the Ru substrate [13,37,38]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“… 31 Klemm et al explored mesoscale structures in the presence of large step bunches and concluded that monolayer phases were prevalent near these step bunches. 32 Because those studies were performed with LEEM/PEEM, it was not possible to discern individual atomic steps or the prevalence of coexisting phases with smaller domain sizes. Here we extend the previous observations by looking at mesoscale structural diversity in the presence of atomic scale single steps and using STM to examine smaller domain sizes.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work it has been reported that holes form during the annealing process and that, once formed, these holes cannot fill up through additional silicon deposition and subsequent oxidation. 32 Nonetheless, the change in crystallinity for the bilayer near the hole edge compared to “inland” bilayer ring distributions suggests that structural rearrangements of the silica bilayer near hole boundaries can occur during the hole formation process or may indicate that holes preferentially form in regions with lower local crystallinity. A previous study by Malashevich et al using density functional theory concluded that deviations from the crystalline hexagonal structure would be expected at lower SiO 2 density in bilayer silica due to surface and interfacial tensions.…”
Section: Resultsmentioning
confidence: 99%
“…One of the evidences of the deconnexion at the BL coverage is the loss of Si-O-Ru perpendicular vibrations modes as demonstrated by Infrared Reflection Absorption Spectroscopy (IRAS) measurements and confirmed by corresponding DFT calculations. 14,15,24,26,27,43 Binding energy (eV) Intensity (a.u.) In a first experimental setup, a ML-film was elaborated following the preparation method described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%